(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article discusses the political ideology and its structure, categories and tasks, the manifestation of conservatism as a political ideology and its characteristics, and the factors affecting its ideological-political evolution are theoretically analyzed.